Investigating Students’ Needs for Effective English Online Learning During Covid-19 for Polbeng Students - Arita Destianingsih; Ari Satria (ELT-Lectura, 2020)
Abstract: The aim of this study is to investigate the students needs for effective English online learning during Covid-19 for State Polytechnic of Bengkalis students. Descriptive survey method was used to find out the target needs and learning needs related to online learning. The data collection used was questionnaire with random samples of 116 students from five different study program. The result of the finding revealed that there were several tools that can be used during online class by considering both students and teachers internet access. The effective tools that can be utilized in explaining the subject and as the virtual tool to replace face to face meeting is Zoom application, while to share and submit the assignment the students preferred Google classroom and WhatsApp. Numerous activities and learning input are also highlighted in order to engage the students to be active in online class. The teachers roles in online class is pointed.